Can Strong Boards and Trading Their Own Firm’s Stock Help CEOs Make Better Decisions? Evidence from Acquisitions by Overconfident CEOs - Kolasinski, Adam C.; Li, Xu (Journal of Financial and Quantitative Analysis, 2013)
Abstract Little evidence exists on whether boards help managers make better decisions. We provide evidence that strong and independent boards help overconfident chief executive officers (CEOs) avoid honest mistakes when they seek to acquire other companies. In addition, we find that once-overconfident CEOs make better acquisition decisions after they experience personal stock trading losses, providing evidence that a manager’s recent personal experience, and not just educational and early career experience, influences firm investment policy. Finally, we develop and validate a new CEO overconfidence measure that is easily constructed from machine-readable insider trading data, unlike previously used measures.